Anatomical and biochemical characterization of the calcium effect on eucalyptus urophylla callus morphogenesis in vitro - Arruda, S. C C; Souza, G. M. [UNESP]; Almeida, M.; Gonçalves, A. N. (Springer Nature, 2000)
Calcium chloride concentrations from 0.0 to 12.12 mM were added to the culture medium and calcium content in calluses were determined directly by X-ray fluorescence spectrometry, a non-destructive method, allowing the processing of the same tissue for histological analysis. A multivariate statistical analysis (PCA - Principal Components Analysis) grouped the treatments into 5 blocks and indicated the most responsive group. Lack of calcium supply caused a complete absence of a morphogenic process and tissue collapse. An increase in calcium concentration gave higher total protein and sugar contents, an increase in peroxidase specific activity and changes in the histological characteristics. It was possible to verify that calcium stimulated globular somatic embryo formation at concentration of 6.62 mM.
Keywords: Histology; Peroxidase specific activity; Protein; Somatic embryogenesis; Sugar; Eucalyptus; Eucalyptus urophylla